Work–family enrichment, job satisfaction, and work engagement: The mediating role of subjective career success - Eileen Koekemoer; Chantal Olckers; Cherise Nel (Australian Journal of Psychology, 2020)
Objective: The aim of the study was to explore the possible indirect effect of subjective career success on the relationship between work–family enrichment and job satisfaction and work–family enrichment and work engagement. Method: A cross‐sectional, quantitative research design approach was followed using a convenience sample (N = 334). Results: Results revealed that work–family enrichment was not only positively related to subjective career success, job satisfaction and work engagement, but also predictive of the mentioned constructs. Furthermore, subjective career success was found to indirectly effect the relationship between work–family enrichment and job satisfaction and work engagement. Conclusion: Using the resource‐gain‐development framework, new insights are provided into the processes and mechanisms relating to work–family enrichment. Our findings suggest that resources are creating positive affect in not only the work and career domains of employees, but also leading to more engaged and satisfied employees. (i.e., the indirect effect of subjective career success). Organisations can benefit when they enhance work environments (e.g., by providing relevant resources) to promote work–family enrichment and, by implication, subjective career success and positive work outcomes such as job satisfaction and work engagement.